Surface-enhanced Raman Scattering (SERS) Substrate of Colloidal Ag Nanoparticles Prepared by Laser Ablation for Ascorbic Acid Detection - Teguh Endah Saraswati; Yudha Pratama Putra; Mohammad Rifqi Ihsan; Isnaeni Isnaeni; Yuliati Herbani (Universitas Jenderal Soedirman, 2018)
Ag nanoparticles were synthesized by laser ablation using an Ag plate in distilled water. This method was performed using a laser with a wavelength of 532 nm and energy of 30 mJ for 60 min. Ag nanoparticles successfully formed, confirmed by the selected area electron diffraction (SAED) which revealed four principal crystal planes of (111), (200), (220) and (311). The size distribution of Ag nanoparticles ranged from 5 to 40 nm, as estimated from electron imaging observed by transmission electron microscope (TEM). Ascorbic acid was used as the analyte to test the characteristics of surface-enhanced Raman scattering (SERS) of colloidal Ag nanoparticles. The concentration of ascorbic acid (1.0, 0.5 and 0.25 wt%) and incubation time (0 and 6 h) were varied to determine the limit of detection and the effect of incubation time. The Raman scattering spectroscopy results showed that the colloidal Ag nanoparticle substrate improved the signals for detection of ascorbic acid.